Readmission Rates for Cruciate-Retaining Total Knee Arthroplasty - Issa, Kimona; Cherian, Jeffrey J.; Kapadia, Bhaveen H.; Robinson, Kristin; Bhowmik-Stoker, Manoshi; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2015)
Currently, the readmission rates for patients treated with cruciate-retaining (CR) prostheses have not been widely evaluated. The purpose of this study was to report on readmission rates after CR total knee arthroplasties (TKAs) and to evaluate the potential contributing factors for these events. We reviewed a prospectively collected database of 412 patients (441 TKAs) at 11 institutions. This included 170 men and 242 women who had a mean age of 66 years. Overall, there were 15 unplanned readmissions (3.4%) in 15 patients during the first 90 days following discharge after the index arthroplasty procedure. This included a readmission rate of 2% at 30 days and 3.2% at 60 days after discharge. Of the 15 readmissions, nine were due to general medical-related causes, while the other six events were as a result of operative site or surgery-related complications. However, readmitted patients had a 29.8% higher incidence of cardiovascular disorders at baseline compared with the patients who were not readmitted. The 30- and 90-day readmission rates for patients treated with cruciate-retaining (CR) TKAs are encouraging since these are comparable to previously reported readmission rates of other prostheses. Unplanned hospital readmissions are expensive and an undesired outcome for the patient, physician, and health care system. The authors believe that the positive mid-term clinical performance of this CR prosthesis may have contributed to the lower readmission rates, and believe that this is a stepping stone for further larger prospective studies and is necessary to better evaluate these findings.
Keywords: hospital readmission; total knee arthroplasty; cruciate-retaining